Injectable composite bone graft material and preparation method thereof
By combining beef bone meal and pearl powder with gelatin and citric acid solutions, an injectable composite bone graft material is solved, and the problems of inconvenient operation and bone resorption of existing bone graft materials are achieved, achieving efficient and stable bone graft effect and low cost.
Patent Information
- Application Number
- CN202411483882.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The existing bone graft materials have defects such as inconvenience in maxillary sinus lifting, susceptibility to gasification, and the inability to maintain spatial stability. It is urgent to develop a new composite bone graft material to improve surgical results and reduce surgical results. cost.
Bovine bone meal and pearl powder are used as mixed powders, and gelatin and citric acid solutions are combined to form a composite solution. The two are mixed by injection to form a composite slurry and solidify under constant temperature conditions to prepare injectable composite bone graft material.
This material has good osteogenic properties, suitable degradation and absorption rate, high mechanical strength, easy to operate, low cost, can effectively improve surgical results and reduce costs.
Smart Images

Figure CN119386274A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of bone transplant materials, and in particular to an injectable composite bone transplant material and a preparation method thereof. Background Art
[0002] With the popularity of oral implant surgery, maxillary sinus floor augmentation is widely used in patients with insufficient residual bone in the maxillary posterior teeth area. This surgery increases the bone volume between the alveolar ridge top and the maxillary sinus floor by implanting bone graft material between the maxillary sinus floor and the augmented mucosa to facilitate dental implant surgery.
[0003] For maxillary sinus floor augmentation, the ideal bone transplant material needs to have the following properties: no risk of immune rejection or bacterial infection, able to adapt to the host bone defect environment and undergo bone integration, able to be replaced by new bone and gradually degraded, and also have some or all of the basic biological properties of bone transplant materials: osteoinductivity, osteoconductivity, and bone regeneration.
[0004] In clinical maxillary sinus augmentation surgery, bone transplant materials such as autologous bone, allogeneic bone, xenogeneic bone and synthetic bone are often used to increase the bone mass of the maxillary sinus floor. However, all types of bone transplant materials are granular, which makes it inconvenient for doctors to operate when implanted into the maxillary sinus floor through the alveolar ridge. The bone transplant materials at the maxillary sinus floor are easily affected by maxillary sinus pneumatization, resulting in bone reabsorption and unable to maintain good spatial stability. There is an urgent need to develop a new type of composite bone transplant material to improve surgical effects and reduce costs. Summary of the invention
[0005] The purpose of the present application is to provide an injectable composite bone transplant material and a preparation method thereof, wherein the material has the advantages of good osteogenic performance, appropriate degradation and absorption rate, high mechanical strength, and convenience for surgical operation, and the material has low cost and can be applied to maxillary sinus augmentation surgery, and can effectively improve the surgical effect.
[0006] The technical solution of this application is as follows:
[0007] On the one hand, the embodiment of the present application provides an injectable composite bone graft material, which is prepared from raw materials including the following components: a mixed powder and a composite solution;
[0008] The raw materials of the mixed powder include cattle bone powder and pearl powder;
[0009] The raw materials of the composite solution include gelatin solution and citric acid solution.
[0010] Furthermore, in some embodiments of the present application, in the above-mentioned mixed powder, the mass ratio of pearl powder is 25-40%;
[0011] In the above-mentioned composite solution, the volume ratio of gelatin solution is 15-35%.
[0012] Furthermore, in some embodiments of the present application, in the mixed powder, the bovine bone powder is prepared by calcining and grinding bovine femur, and the pearl powder is pharmaceutical grade pearl powder.
[0013] Further, in some embodiments of the present application, in the above-mentioned composite solution, the gelatin solution used is prepared from dry gelatin, and its concentration is 11.11%;
[0014] The concentration of the citric acid solution used was 25%.
[0015] Furthermore, in some embodiments of the present application, in the raw material components, the solid-liquid ratio of the mixed powder to the composite solution is 0.35 mL / g.
[0016] On the other hand, the present invention also provides a method for preparing the above-mentioned injectable composite bone graft material, which comprises the following steps:
[0017] Preparation of cattle bone powder: Take cattle bones and remove impurities such as surface muscle, periosteum, fat, etc., boil them in water, soak them in sodium hydroxide solution and hydrogen peroxide solution respectively, wash them, calcine them, grind them and sieve them to obtain cattle bone powder for later use;
[0018] Preparation of mixed powder: Mix the prepared cow bone powder and pearl powder in proportion to obtain a mixed powder for later use;
[0019] Preparation of gelatin solution: weigh dry gelatin and add UP water to make the dry gelatin swell to a gel state, then perform constant temperature treatment to prepare a gelatin solution for later use;
[0020] Preparation of composite solution: Mix the prepared gelatin solution with the citric acid solution in proportion to obtain a composite solution for later use;
[0021] Product material preparation: The prepared mixed powder is mixed with the composite solution in proportion to obtain a composite slurry, and the composite slurry is then injected into a mold and then cured at a constant temperature to obtain the product injectable composite bone transplant material.
[0022] Furthermore, in some embodiments of the present application, in the above-mentioned cattle bone powder preparation step, the concentration of the sodium hydroxide solution used is 1 mol / L, and the concentration of the hydrogen peroxide used is 30%.
[0023] Furthermore, in some embodiments of the present application, in the above-mentioned cattle bone powder preparation step, calcination is carried out in a muffle furnace at 850° C., and then grinding is carried out in a planetary ball mill at a rate of 50 r / min, and the cattle bone powder is obtained after sieving.
[0024] Furthermore, in some embodiments of the present application, in the above-mentioned gelatin solution preparation step, the gelatin solution is prepared by constant temperature treatment in a 37° C. electric thermostat.
[0025] Furthermore, in some embodiments of the present application, in the above-mentioned product material preparation step, constant temperature curing is carried out in an electric constant temperature forced air drying oven at a temperature of 37° C. and a humidity of 100% to obtain a product injectable composite bone transplant material.
[0026] Compared with the prior art, the embodiments of the present application have at least the following advantages or beneficial effects:
[0027] In view of the above aspects, the embodiments of the present application provide an injectable composite bone graft material and a preparation method thereof, wherein the product bone graft material is modified to be injectable using bovine bone powder as a base material, and a mixed powder of bovine bone powder / pearl powder and a gelatin / citric acid composite solution are combined to form a composite slurry, which can effectively retain organic components such as water-soluble proteins in pearl powder, thereby improving the biocompatibility and osteoinduction of the new composite bone cement; and by compounding the gelatin solution with the citric acid solution, the anti-collapse and mechanical strength of the product bone graft material can be effectively improved.
[0028] Compared with the commonly used commercial granular bone transplant materials on the market, the product material provided in this application has better cell compatibility, cell adhesion and induction of cell osteogenic properties. It is low-cost and has excellent performance, and has great application potential in maxillary sinus floor augmentation surgery. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 This is a schematic diagram of the degradation rate in the in vitro degradation rate determination of Experimental Example 1;
[0031] Figure 2 This is a schematic diagram of the degradation situation in the in vitro degradation rate determination of Experimental Example 1;
[0032] Figure 3 This is a schematic diagram of the degradation rate in the in vitro degradation rate determination of Experimental Example 2;
[0033] Figure 4 This is a schematic diagram of the degradation situation in the in vitro degradation rate determination of Experimental Example 2;
[0034] Figure 5 This is the SEM scan image in Experimental Example 3;
[0035] Figure 6 This is the EDS test result diagram in Experimental Example 3;
[0036] Figure 7 Schematic diagram of the mass ratio of elements in Experimental Example 3;
[0037] Figure 8 This is the infrared spectrum of Experimental Example 3;
[0038] Fig. 9 This is the XRD test result diagram in Experimental Example 3;
[0039] Fig.10 It is the particle size distribution diagram in Experimental Example 3;
[0040] Fig.11 This is a schematic diagram of cell adhesion in Experimental Example 4;
[0041] Fig.12 This is a schematic diagram of cell proliferation in Experimental Example 4;
[0042] Fig.13 This is the standard protein concentration curve in Experimental Example 4;
[0043] Fig.14 Schematic diagram of protein concentration and relative activity level of ALP in Experimental Example 4;
[0044] Fig.15 Schematic diagram of the slurry morphology in Experimental Example 5. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0046] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application may be combined with each other.
[0047] The features and performance of the present application are further described in detail below in conjunction with the embodiments.
[0048] Example 1
[0049] This embodiment provides a cattle bone meal, which is prepared by the following method:
[0050] The commercially available bovine femur was removed of organic impurities such as muscle, periosteum and fat, boiled in water for 8 hours to completely remove grease, immersed in 1 mol / L NaOH solution for 36 hours, and after immersion, the NaOH on the surface of the bovine femur was washed off with ultrapure water (UP), and then the washed bovine femur was immersed in 30% hydrogen peroxide solution for 36 hours to remove residual grease in the pores of the bovine femur. After immersion, the bovine femur was washed three times with UP water and set aside.
[0051] The treated bovine femur was then calcined in a muffle furnace at 850°C for 3 hours, and then the calcined bovine femur was placed in a planetary ball mill and ground at a rate of 50 r / min for 1 hour, and sieved to obtain bovine bone powder.
[0052] Example 2
[0053] This embodiment provides an injectable pearl powder / bovine bone powder composite bone transplant material, which is prepared by the following method:
[0054] Preparation of mixed powder: Take the cattle bone powder prepared in Example 1, add pearl powder and mix to obtain a mixed powder for later use; wherein the mass ratio of the added pearl powder in the mixed powder is 35%.
[0055] Product material preparation: Add 25% citric acid solution to the prepared mixed powder at a solid-liquid ratio of 0.35mL / g to obtain a composite slurry, and then inject the obtained composite slurry into a cylindrical silica gel model with a diameter of 6mm and a height of 5mm through a 5mL medical syringe, and put it into an electric constant temperature blast drying oven at a temperature of 37°C and a humidity of 100% for curing. After curing, demold and dry to obtain the product bone transplant material.
[0056] Example 3
[0057] This embodiment provides an injectable pearl powder / gelatin / bovine bone powder composite bone transplant material, which is prepared by the following method:
[0058] Preparation of mixed powder: the mixed powder prepared in Example 2.
[0059] Preparation of gelatin solution: Weigh 11.11 g of dry gelatin and add 88.89 mL of UP water. Wait until the dry gelatin is fully swollen to a gel state, seal it in a wide-mouth bottle, and place it in a 37°C electric thermostat for 12 hours to form a gelatin solution with a concentration of 11.11%, which is ready for use.
[0060] Preparation of composite solution: the prepared gelatin solution is mixed with a citric acid solution with a concentration of 35% to obtain a composite solution for standby use; wherein the volume ratio of the added gelatin solution in the composite solution is 35%.
[0061] Product material preparation: Mix the mixed powder and the composite solution at a solid-liquid ratio of 0.35mL / g to obtain a composite slurry, and then inject the obtained composite slurry into a silicone mold through a 5mL medical syringe, and put it into an electric constant temperature blast drying oven at a temperature of 37°C and a humidity of 100% for curing. After curing, demold and dry to obtain the product bone transplant material.
[0062] Experimental Example 1
[0063] The purpose of this experimental example is to optimize the ratio of cattle bone powder to pearl powder;
[0064] On the basis of the scheme of Example 2, the proportion of pearl powder added in the mixed powder preparation step was changed to prepare multiple groups of pearl / bovine bone powder composite bone transplant materials, and the performance of each group of product materials was tested.
[0065] The amount of pearl powder added in each group is shown in Table 1:
[0066] Table 1
[0067] Group Pearl powder / wt% Remark 1 0 No pearl powder added 2 25 / 3 30 / 4 35 Same as Example 2 5 40 / 6 45 / 7 50 /
[0068] The injectability rate of each group of product materials is determined as follows:
[0069] A 5mL syringe filled with pearl / bovine bone powder composite slurry is fixed vertically on the base of the universal mechanical testing machine, and a force of 1mm / min is applied to the plunger of the syringe. The test ends when the force reaches 100N. The injectability formula of the material is as follows:
[0070]
[0071] M0 is the mass of the syringe itself, M1 is the mass of the syringe after the composite slurry is filled, and M2 is the mass of the syringe after the test is completed.
[0072] Each group of samples was tested three times, the average value was taken, and the composite slurry with a high injectability rate was selected for subsequent research.
[0073] The results are shown in Table 2:
[0074] Table 2
[0075]
[0076]
[0077] Note: a: Group N VS Group 1, P < 0.05; b: Group N VS Group N+1, P < 0.05
[0078] The results show that when the pearl powder addition ratio is 25%-35%, there is no statistically significant difference in the injection rate of the pearl / bovine bone powder composite slurry and the injectability rate of the bovine bone powder slurry (P>0.05); when the pearl powder addition ratio is 40%-50%, the amount of pearl powder added increases, and the injectability of the pearl / bovine bone powder composite slurry decreases accordingly, and the difference in injectability among the groups is statistically significant (P<0.05).
[0079] The injectability of the slurry is related to factors such as the distance between solid phase particles and the solid-liquid ratio. When the pearl powder is added at a ratio of 40%-50%, the pearl powder increases the distance between the composite powders, thereby making the citrate and Ca 2+ The cross-linking entanglement distance increases, so the composite powder cannot be completely cross-linked and entangled at a solid-liquid ratio of 0.35mL / mg, causing the pearl / bovine bone powder composite slurry within this range to experience solid-liquid separation. In this experiment, when the addition ratio of pearl powder was 0-35%, the composite slurry showed a good injectability rate, and the 2nd, 3rd and 4th groups of injectable pearl / bovine bone powder composite bone transplant materials were selected for intensive research.
[0080] The solidification time of each group of product materials is measured. The specific method is as follows:
[0081] The Gillmore double needle method was used: a homemade thick needle with a mass of 113 g and a diameter of 2.1 mm was used to measure the initial setting time, and a homemade thin needle with a mass of 445 g and a diameter of 1.1 mm was used to measure the final setting time. The injectable bone graft material was solidified in an electric constant temperature air-heat drying oven and taken out of the air-heat drying oven every 2 minutes for needle puncture measurement. When there was no obvious needle puncture mark on the surface of the material, the initial setting time (T I ) and final setting time (T F ), each group of samples was tested 3 times and the average value was taken. According to clinical requirements: 3min≤T I ≤8min, T F The injectable pearl / bovine bone powder composite bone graft materials in each group were evaluated for ≤15min.
[0082] The results are shown in Table 3:
[0083] Table 3
[0084]
[0085]
[0086] Note: a: P<0.05 for group N vs. group 1, b: P<0.05 for group N vs. group N+1
[0087] The results show that when the mass ratio of pearl powder added is 0%-35%, the T of the injectable pearl / bovine bone powder composite bone transplant material is I With T F The difference between the two adjacent groups was statistically significant (P<0.05). When the mass ratio of pearl powder added was 35%-50%, the T I With T F Both increased with the increase of the proportion of pearl powder added, and the difference between the two adjacent groups was statistically significant (P<0.05).
[0088] The setting time of injectable bone graft materials is also related to factors such as the distance between solid phase particles, solid-liquid ratio, viscosity, and the type of additives. In this experiment, the bovine bone powder slurry has a low viscosity and takes a long time to set; the injectable pearl / bovine bone powder composite slurry has a high viscosity. The setting time of injectable pearl / bovine bone powder composite bone graft materials in groups 2-7 is shorter than that of injectable bovine bone powder bone graft materials (P<0.05). As the mass ratio of pearl powder increases, the distance between pearl / bovine bone powder particles increases, so the setting time of 40%-50% injectable pearl / bovine bone powder composite bone graft materials increases. The setting time of injectable bone graft materials in groups 2-7 meets clinical requirements, but the curing time of injectable composite materials in groups 2, 3, and 4 is shorter, and they can quickly solidify to maintain a stable spatial structure at the transplant site, showing good application potential.
[0089] The in vitro degradation rate of each group of product materials was determined as follows:
[0090] The initial mass N0 of each group of injectable bone graft materials after solidification was weighed, and the injectable pearl / bovine bone powder composite bone graft materials were added to the PBS solution (pH=7.4) according to the specification of 0.2g / ml, and transferred to an electric constant temperature air drying oven with a temperature of 37°C and a humidity of 100%. The degradation of the injectable pearl / bovine bone powder composite bone graft materials was observed at 1, 3, 5 and 7 days, and the materials were taken out and dried at the above 5 time points and weighed and recorded as N x The degradation rate of each group at different times was calculated by the following formula. Each group of samples was tested 3 times and the average value was taken.
[0091]
[0092] The results are as follows Figure 1 and Figure 2 As shown:
[0093] Figure 1 The figure is a schematic diagram of the degradation rate of injectable bone graft materials of groups 1-7 in PBS solution within 7 days; in the figure, a represents group N VS group 1, P < 0.05, and b represents group N VS group N+1, P < 0.05.
[0094] Figure 2 It is a schematic diagram of the degradation of the injectable bone graft materials of groups 1-7 after solidification within 7 days; in the figure, AD on the left side respectively represents the degradation of the injectable bone graft materials of each group at 1, 3, 5, and 7 days.
[0095] Figure 1 The degradation rates of the seven groups of injectable bone graft materials after solidification and addition of PBS solution increased with time (P<0.01). Figure 2 The figure shows the degradation of 7 groups of injectable bone graft materials under naked eye observation: the degradation rate of injectable bovine bone powder bone graft materials in Group 1 was low (P<0.05), and the degradation rate on the 7th day was 15.41±0.27%; the degradation rate of injectable pearl / bovine bone powder composite bone graft materials in Groups 2-7 decreased with the increase of pearl mass ratio (P<0.05), and the degradation rate of injectable pearl / bovine bone powder composite bone graft materials in Group 2 was 63.98±0.70% on the 7th day, and the degradation rate of injectable pearl / bovine bone powder composite bone graft materials in Group 7 was 24.14±0.38% on the 7th day.
[0096] The degradation rate of injectable bone graft materials is related to factors such as the internal structure of the material, the solidification time, and the spacing between solid phase particles: In this experiment, the injectable bone graft materials produced pore structures during the solidification process, so the injectable bone graft materials in groups 1-7 all had a certain degradation rate after solidification. The injectable bone graft materials in groups 1, 5, 6, and 7 had enough time to cross-link and precipitate a tightly structured surface during the solidification process, which could prevent the infiltration of PBS and cause less degradation of the bone graft materials. The injectable bone graft materials in groups 2, 3, and 4 had a short solidification time, and did not have enough time to cross-link and precipitate a tightly structured surface during the solidification process to effectively prevent the infiltration of PBS solution, causing obvious degradation of the bone graft materials. The ideal injectable bone graft material should have a degradation rate consistent with the rate of new bone formation at the transplant site, providing a stable space for the formation of new bone and then being biodegraded and completely replaced by new bone. The degradation rate of the injectable bone graft materials in this experiment was relatively large, and it could not meet the clinical requirements for the degradation rate of bone graft materials. The injectable composite bone graft materials in group 4 with a relatively low degradation rate could be selected for optimization.
[0097] The compressive strength of each group of product materials is measured. The specific method is as follows:
[0098] Before the test, the upper and lower ends of the solidified cylindrical injectable pearl / bovine bone powder composite bone graft material were smoothed with sandpaper, and then the sample was placed on a universal mechanical testing machine to test its compressive strength. The instrument moved at a speed of 0.1 mm / min. When the pressure curve peaked and cracks appeared in the sample material, the test machine was stopped, and the maximum pressure F (N) and compressive strength of the sample material were recorded. Each group of materials was tested three times and the average value was taken. Clinical data showed that the pressure range of the alveolar bone in the posterior teeth area of the maxillary sinus was 4-13 MPa, so the injectable composite bone graft material that met the clinical requirements was selected for subsequent research.
[0099] The results are shown in Table 4:
[0100] Table 4
[0101]
[0102]
[0103] Note: a: Group N VS Group 1, P < 0.05; b: Group N VS Group N+1, P < 0.05
[0104] The results show that the compressive strength of the injectable bovine bone powder bone graft material in group 1 is greater than that of the injectable pearl / bovine bone powder composite bone graft material in groups 2-7 (P<0.05). The compressive strength of the injectable pearl / bovine bone powder composite bone graft material in groups 2-7: As the mass ratio of pearl powder increases, the compressive strength of the injectable pearl / bovine bone powder composite bone graft material increases accordingly. The compressive strength of injectable bone graft materials is affected by factors such as their internal structure and solidification time: the longer the solidification time of the injectable bone graft material, the more time it can provide for the precipitation of solid phase particles and the growth of crystals, which helps to generate large crystalline substances with complete structures inside the injectable bone graft material. Therefore, in this experiment, it was found that the compressive strength of the injectable bone graft materials with long solidification times (Groups 1, 5, 6 and 7) was greater than that of the injectable bone graft materials with short solidification times (Groups 2, 3 and 4): 25%-35% injectable pearl / bovine bone powder composite bone graft materials <45-50% injectable pearl / bovine bone powder composite bone graft materials < injectable bovine bone powder bone graft materials, but the current mechanical strength of the injectable bone graft materials in Groups 1-7 has not reached the compressive strength range (4-13MPa) that the maxillary posterior teeth should withstand clinically. The process of the injectable pearl / bovine bone powder composite bone graft materials in Group 4 with better comprehensive performance can be optimized to improve their compressive strength.
[0105] In summary, seven groups of injectable pearl / bovine bone powder composite bone transplant materials with different pearl powder mass ratios (0%, 25%, 30%, 35%, 40%, 45%, 50%) were tested through experimental methods such as injectability, setting time, degradation rate and compressive strength. The results showed that the composite bone transplant material with 35wt% pearl powder added had better comprehensive performance: the composite slurry had high viscosity, an injectability rate of 98.5±0.10%, an initial setting time of 4.40±0.11min, and a final setting time of 10.44±0.33min. However, its degradation rate was 45.40±0.29% and its compressive strength was 0.75±0.01MPa, which did not meet clinical requirements. The physicochemical properties of the composite bone transplant material could be improved through liquid phase optimization.
[0106] Experimental Example 2
[0107] Based on the conclusion of Experimental Example 1, this Experimental Example adopts the best overall ratio of pearl / cow bone powder (the volume ratio of pearl powder in the mixed powder is 35%, the same as in Example 2) to perform liquid phase optimization.
[0108] That is, on the basis of the scheme of Example 3, the proportion of the gelatin solution added in the composite solution preparation step was changed to prepare multiple groups of pearl / gelatin / bovine bone powder composite bone transplant materials, and the performance of each group of product materials was tested.
[0109] The amount of gelatin solution added in each group is shown in Table 5:
[0110] Table 5
[0111]
[0112]
[0113] The injectability rate of each group of product materials was measured in the same manner as in the injectability rate measurement section of Experimental Example 1;
[0114] The results are shown in Table 6:
[0115] Table 6
[0116] Grouping Gelatin / vol% Injectable rate / % A 0 97.41±0.07 B 15 97.37±0.04 C 25 97.35±0.02 D 35 <![CDATA[97.14±0.04 b ]]> E 45 <![CDATA[96.83±0.02 a,b ]]> F 55 <![CDATA[95.41±0.04 a,b ]]>
[0117] Note: a: P<0.05 when group x VS group A; b: P<0.05 when group x VS group x+1
[0118] The results show that there is no significant difference in the injectability of BD pearl / gelatin / bovine bone powder composite slurry (P>0.05). When the volume ratio of gelatin solution is 15%-25%, there is no statistically significant difference in the injectability of pearl / bovine bone powder composite slurry and pearl / gelatin / bovine bone powder composite slurry (P>0.05). When the volume ratio of gelatin solution is 35%-55%, there is a statistically significant difference in the injectability of pearl / bovine bone powder composite slurry and pearl / gelatin / bovine bone powder composite slurry (P<0.05). Gelatin can improve the viscosity of pearl / gelatin / bovine bone powder composite slurry. As the volume ratio of gelatin increases, the viscosity of pearl / gelatin / bovine bone powder composite slurry increases, thereby reducing the injectability of pearl / gelatin / bovine bone powder composite slurry. The injectability of pearl / gelatin / bovine bone powder composite slurry in this experiment is greater than 95%, and all are easy to inject slurries, which can be used for subsequent research.
[0119] The solidification time of each group of product materials was measured in the same manner as in the solidification time measurement section of Experimental Example 1;
[0120] The results are shown in Table 7:
[0121] Table 7
[0122]
[0123]
[0124] Note: a: P<0.05 when group x VS group A; b: P<0.05 when group x VS group x+1
[0125] The results show that with the increase in the volume ratio of gelatin mixing, the initial setting time and final setting time of the injectable bone graft material after gelatin optimization are prolonged. This may be because gelatin increases the distance between pearl / bovine bone powder particles, thereby increasing the setting time of the injectable pearl / gelatin / bovine bone powder composite bone graft material. Therefore, four groups of injectable pearl / gelatin / bovine bone powder composite bone graft materials A, B, C and D with initial setting time ≤8min and final setting time ≤15min were selected for subsequent experimental research.
[0126] The in vitro degradation rate of each group of product materials was measured using the same method as in the in vitro degradation rate measurement section of Experimental Example 1;
[0127] The results are as follows Figure 3 , Figure 4 As shown:
[0128] Figure 3 This is a schematic diagram of the degradation rate of the injectable pearl / gelatin / bovine bone powder composite bone graft material in group AF within 7 days; in the figure, a represents group N VS group 1, P < 0.05, and b represents group N VS group N+1, P < 0.05.
[0129] Figure 4 This is a schematic diagram of the degradation of the injectable pearl / gelatin / bovine bone powder composite bone graft material in group AF within 7 days; in the figure, left side ad represents the degradation of each group's composite material on the 1st, 3rd, 5th and 7th day, respectively.
[0130] The results show that the injectable pearl / bovine bone powder composite bone graft material in group A degraded significantly in PBS solution, and the degradation rate was 46.49±0.74% after 7 days. When the volume ratio of gelatin solution was 15%-35%, as the volume ratio of gelatin solution increased, the degradation rate of injectable pearl / gelatin / bovine bone powder composite bone graft material in PBS solution decreased, among which the degradation rate of injectable pearl / gelatin / bovine bone powder composite bone graft material in group D was 4.52±0.35% on the 7th day. When the volume ratio of gelatin solution was 45%-55%, the degradation rate of injectable pearl / gelatin / bovine bone powder composite bone graft material increased, and the sample material in group E began to show obvious degradation on the 3rd day, and the sample material in group F showed obvious degradation on the 5th day. Both groups of materials were finally completely degraded on the 7th day. The reasons for the change in the degradation rate of the injectable pearl / gelatin / bovine bone powder composite bone graft material are as follows: when the volume ratio of the gelatin solution is 15%-35%, the gelatin in the gelatin-citric acid composite liquid phase has a strong viscosity, which increases the adhesion between the injectable pearl / bovine bone powder particles and improves the degradation resistance of the injectable pearl / gelatin / bovine bone powder composite bone graft material; but when the volume ratio of the gelatin solution is 45%-55%, the injectable pearl / gelatin / bovine bone powder composite bone graft material shows obvious degradation, which may be because the gelatin solution adheres to a large amount of pearl / bovine bone powder, which increases the Ca 2+ The cross-linking entanglement distance of the ester bond with the citric acid solution caused the cured injectable pearl / gelatin / bovine bone powder composite bone graft material to completely degrade in the PBS solution. Therefore, the injectable pearl / gelatin / bovine bone powder composite bone graft materials of groups B, C and D with low degradation rates were selected for subsequent experimental studies.
[0131] The compressive strength of each group of products was measured using the same method as in the compressive strength measurement section of Experimental Example 1;
[0132] The results are shown in Table 8:
[0133] Table 8
[0134] Grouping Gelatin / vol% Maximum pressure / N Compressive strength / MPa A 0 20.83±0.26 0.74±0.01 B 15 <![CDATA[153.73±0.40 a,b ]]> <![CDATA[5.49±0.01 a,b ]]> C 25 <![CDATA[210.92±0.20 a,b ]]> <![CDATA[7.53±0.01 a,b ]]> D 35 <![CDATA[234.62±0.92 a,b ]]> <![CDATA[8.38±0.03 a,b ]]> E 45 <![CDATA[224.73±3.03 a,b ]]> <![CDATA[8.03±0.11 a,b ]]> F 55 <![CDATA[181.15±0.14 a,b ]]> <![CDATA[6.47±0.01 a,b ]]>
[0135] Note: a: P<0.05 when group x VS group A; b: P<0.05 when group x VS group x+1
[0136] The results showed that the compressive strength of the injectable pearl / gelatin / bovine bone powder composite bone graft material was greater than that of the injectable pearl / bovine bone powder composite bone graft material (P<0.05). When the volume ratio of gelatin solution was 15%-35%, the compressive strength of the injectable pearl / gelatin / bovine bone powder composite bone graft material increased with the increase of the volume ratio of gelatin solution; when the volume ratio of gelatin solution was 45%-55%, the compressive strength of the injectable pearl / gelatin / bovine bone powder composite bone graft material decreased with the increase of the volume ratio of gelatin solution. The possible reason is that when the gelatin solution is added at a volume ratio of 15%-35%, the cohesiveness of pearl / bovine bone powder is increased, the movement of pearl / bovine bone powder particles is restricted, and the compressive strength of the injectable pearl / gelatin / bovine bone powder composite bone graft material is improved. However, the gelatin solution with a larger volume ratio occupies too many gaps in the pearl / bovine bone powder particles, and the gelatin-citric acid composite solution cannot build a strong cross-linking structure with the composite powder, thereby causing the compressive strength of the injectable pearl / gelatin / bovine bone powder composite bone graft material to decrease. Therefore, the injectable pearl / gelatin / bovine bone powder composite bone graft material of group D with the largest compressive strength was selected for subsequent experimental research.
[0137] In summary, the physicochemical properties of injectable pearl / gelatin / bovine bone powder composite bone transplant materials with 6 groups of different gelatin volume ratios (0%, 15%, 25%, 35%, 45%, 55%) were measured by injectability rate, coagulation time, degradation rate and compressive strength. The results showed that the comprehensive performance of the 35 vol% gelatin group was better: the injectability rate reached 97.14±0.04%, the initial coagulation time was 7.21±0.04min, the final coagulation time was 12.89±0.26min, the degradation rate decreased from 45.40±0.29% to 4.52±0.35% (P<0.05), and the compressive strength increased from 0.75±0.01MPa to 8.38±0.03MPa.
[0138] Experimental Example 3
[0139] Three groups of injectable bone transplant materials were selected, namely, a bovine bone powder group (same as in Example 1), a 35 wt% pearl powder compound group (same as in Example 2), and a 35 vol% gelatin optimization group (same as in Example 3). The physical and chemical properties were characterized by SEM, ESD, FT-IR, XRD, and particle size detection methods. The specific test items, test methods, and test results are as follows:
[0140] SEM test:
[0141] The three groups of injectable bone graft materials were placed on the conductive glue on the sample stage, and the surface morphology of the materials was observed and the pore size range was measured at 500 and 3500 times magnification under an accelerating voltage of 10 kV.
[0142] The results are as follows Figure 5 As shown:
[0143] Figure 5 The SEM scans of three groups of injectable bone transplant materials, in which A / B are 500 times and 3500 times SEM images of the bovine bone powder group (same as Example 1), C / D are 500 times and 3500 times SEM images of the pearl / bovine bone powder group (same as Example 2), and E / F are 500 times and 3500 times SEM images of the pearl / gelatin / bovine bone powder group (same as Example 3). The blue arrows indicate disc-shaped crystals, and the red arrows indicate needle-shaped crystals.
[0144] The results show that the three groups of injectable bone graft materials have pore structures inside when observed at 500 times magnification. Figure 5 A) has a pore size range of 42.73um to 99.01um, and can be used to inject pearl / bovine bone powder composite bone transplant material ( Figure 5 C) The pore size range is 96.88um to 288.31um, and the pearl / gelatin / bovine bone powder composite bone graft material can be injected ( Figure 5 E) The pore size range is 75.94um to 208.62um. The pore size of the injectable bone graft material is related to factors such as reaction temperature and coagulation time. The reaction degree of bovine bone powder with citric acid solution is low and the heat release is small, so the internal pore size of the injectable bovine bone powder bone graft material is the smallest. The reaction degree of pearl / bovine bone powder with citric acid solution is high and the heat release is large, so the pore size of the two groups of injectable composite bone graft materials is larger than that of the injectable bovine bone powder bone graft material. In addition, the gelatin in the injectable pearl / gelatin / bovine bone powder composite bone graft material increases the distance between the pearl / bovine bone particles and increases its coagulation time, allowing CO2 bubbles to have enough time to escape, so the pore size formed is smaller than that of the injectable pearl / bovine bone powder composite bone graft material. Studies have shown that pore sizes greater than 50um are conducive to blood flowing into the bone graft material and improving the bone induction ability of the bone graft material. A pore size ranging from 200um to 300um can also maintain a certain mechanical strength. The pore size of the injectable composite bone graft material prepared in this scheme meets the pore size range specified above.
[0145] Under magnification of 3500 times, disc-shaped crystals were observed to precipitate inside the pores of the injectable bovine bone powder bone graft material ( Figure 5 B), disc-shaped crystal clusters are precipitated inside the pores of the injectable pearl / bovine bone powder composite bone graft material ( Figure 5 D), after optimization, the injectable pearl / gelatin / bovine bone powder composite bone graft material has gelatin fibers attached to the surface, and needle-like crystals precipitate around the gelatin fibers ( Figure 5F). The disc-shaped crystals may be carbonate apatite crystals, and the needle-shaped crystals may be calcium-deficient apatite crystals. The reasons for the different forms of crystals in the pore structures of the three groups of injectable bone graft materials may be: the disc-shaped crystals in the injectable bovine bone powder bone graft material and the injectable pearl / bovine bone powder composite bone graft material may be disc-shaped carbonate apatite crystals, and CO3 is generated during the dissolution of the composite powder by citric acid liquid phase. 2- ,CO3 2- Can react with PO4 in hydroxyapatite 3- The amount of carbonate apatite crystals may be related to the CO3 2- It is related to the replacement amount of HA: HA in calcined bovine bone powder dissolves in citric acid liquid phase to produce CO3 2- The amount is small, and the carbonate apatite crystals obtained by replacement with HA are small. The pearl / cow bone powder composite solid phase dissolved in citric acid solution can produce more CO3 2- In the injectable pearl / bovine bone powder composite bone graft material, more carbonate apatite crystals can be replaced. In the injectable pearl / gelatin / bovine bone powder composite bone graft material, gelatin contains COO-, which can preferentially react with Ca in pearl / bovine bone powder during the curing process. 2+ It acts to promote the precipitation of needle-shaped calcium-deficient apatite crystals around the gelatin fibers.
[0146] EDS Test:
[0147] The Thermo Fisher scanning electron microscope was switched to EDS test mode, and the element ratios of the above three groups of injectable bone graft materials were analyzed in the surface area, and the calcium-phosphorus ratios of the three groups of injectable bone graft materials were calculated.
[0148] The results are as follows Figure 6 , Figure 7 As shown:
[0149] Figure 6 The EDS test results of three groups of injectable bone transplant materials are shown in Figure 1, where A is the bovine bone powder group (same as Example 1), B is the pearl / bovine bone powder group (same as Example 2), and C is the pearl / gelatin / bovine bone powder group (same as Example 3).
[0150] Figure 7 Schematic diagram of the element mass ratio of three groups of injectable bone graft materials.
[0151] Depend on Figure 6 It can be seen that there are four main elements in each group of injectable bone graft materials, namely Ca, P, C and O. Statistical analysis of the element proportions of the three groups of injectable bone graft materials Figure 7As shown: The Ca / P ratio of injectable bovine bone powder bone graft material is 2.01±0.17, which is similar to the calcium-phosphorus ratio of human bones. Pearl powder is added to the injectable pearl / bovine bone powder composite bone graft material, and the mass ratio of Ca element is 54.30±0.53%, which is higher than that of injectable bovine bone powder bone graft material (P<0.01), and the Ca / P ratio is increased to 3.02±0.42. The injectable pearl / gelatin / bovine bone powder composite bone graft material contains gelatin solution, so the mass ratios of C element and O element are 13.82±0.09% and 51.20±0.38%, respectively, which are higher than those of the other two groups of injectable bone graft materials (P<0.01). The Ca / P ratio of this group of injectable composite bone graft materials is 4.05±0.18, which is significantly different from the calcium-phosphorus ratio of the other two groups (P<0.05). The calcium-phosphorus ratio has a certain influence on the mechanical strength of the injectable bone graft material. The mechanical strength increases with the increase of the calcium-phosphorus ratio. Therefore, the injectable pearl / gelatin / bovine bone powder composite bone graft material shows better compressive resistance than the other two groups of injectable bone graft materials.
[0152] FT-IR test:
[0153] Potassium bromide was added to the three groups of injectable bone graft materials mentioned above, and then ground into fine powder and pressed into tablets. Then, the tablets were scanned in the range of 4000-450 cm -1 The components of each group of injectable bone graft materials were tested.
[0154] The results are as follows Figure 8 As shown:
[0155] Figure 8 ] are infrared spectra of three groups of injectable bone transplant materials. In the figure, red represents the bovine bone powder group (same as Example 1), green represents the pearl / bovine bone powder group (same as Example 2), and black represents the pearl / gelatin / bovine bone powder group (same as Example 3).
[0156] As can be seen from the figure, 470cm -1 , 473cm -1 The stretching vibration peak of Ca-O can be observed at 712 cm -1 The peak at represents CO3 2- The vibration of 980 cm is a unique signature of pearl aragonite. -1 HPO4 2- The stretching vibration peak is 1276cm -1 The vibration peak of the carboxyl bond in citric acid can be observed at 1303cm -1 The peak at 1787 cm represents the CO bond between the hydroxyl group and the carbon atom. -1 The peak at represents CO3 2- C=O group in 1988cm -1The triplet peak is the stretching vibration of OH in carbonated hydroxyapatite, 2546 cm -1 The peak at 2922 cm is attributed to the v(CH) of the organic matrix in the pearl powder. -1 There is a stretching vibration peak of CH in HA at 3080cm -1 The weak peak at 3400 cm-1 is derived from the v(NH) of amide B, representing the presence of gelatin. -1 , 3570cm -1 The peak at represents the stretching vibration of OH. The main components of each group of injectable bone graft materials need to be confirmed in combination with XRD test results.
[0157] XRD test:
[0158] The three groups of injectable bone transplant materials were subjected to XRD detection: the instrument light source was Cu-Ka, the scanning range was 10-80°, and the scanning mode was continuous scanning.
[0159] The results are as follows Fig. 9 As shown:
[0160] Fig. 9 Graphs showing the XRD test results for three groups of injectable bone transplant materials. In the graphs, red represents the bovine bone powder group (same as in Example 1), green represents the pearl / bovine bone powder group (same as in Example 2), and black represents the pearl / gelatin / bovine bone powder group (same as in Example 3).
[0161] As can be seen from the figure, compared with the standard card PDF, the three groups of injectable bone graft materials all showed (002), (121), (120) and (300) diffraction peaks, which are characteristic peaks of HA (JCPDF84-1998). The (300) diffraction peak was introduced at 2θ=32.1°, indicating that PO4 3- By CO3 2- The two groups of injectable pearl / bovine bone powder composite bone graft materials showed diffraction peaks (111), (102), (112) and (221), which are characteristic peaks of pearl aragonite (JCPDF75-2230). The diffraction peaks (100), (111) and (120) are characteristic peaks of brushite (JCPF83-1888).
[0162] The characterization results reflect the hydrolysis and curing mechanism of the optimized injectable composite bone graft material prepared in this application: citric acid solution is used as a common blending liquid for the solid phase of injectable bone graft materials. The solution is acidic and can dissolve pearl powder and bovine bone powder to generate Ca 2+ 、HPO4 2- PO4 3- and CO3 2-Plasma promotes the recombination of these ions to form new hydroxyapatite, calcium hydrogen phosphate and carbonate apatite crystals, which eventually solidify into pearl / bovine bone powder composite bone graft material as the crystals grow.
[0163] Particle size test:
[0164] After drying, the bovine bone powder (same as in Example 1) and pearl / bovine bone powder (same as in Example 2) were placed in a four-way quartz cuvette with a light path of 10 mm, 1 mL of PBS solution was added to disperse them evenly, and the particles were placed in a Zeta particle size analyzer to detect the particle size of the solid powder material.
[0165] The results are as follows Fig.10 As shown:
[0166] Fig.10 1 is a particle size distribution diagram of cattle bone meal (same as Example 1) and pearl / cattle bone meal (same as Example 2). In the diagram, the yellow oblique line area represents cattle bone meal, and the green area represents pearl / cattle bone meal.
[0167] It can be seen from the results that the particle size of calcined bovine bone powder is 1.16±0.05um, and the particle size of pearl / bovine bone powder is 1.8±0.03um. The addition of pearl powder can significantly increase the particle size of the composite powder (P<0.05). The particle size of the powder will also affect the injection rate of the injectable bone transplant material: when the solid phase particle size is micron, the injection rate of the injectable bone transplant material is high. The micron-grade pearl / bovine bone powder prepared in this application can be used for the research and development of injectable bone transplant materials.
[0168] In summary, through the characterization of the physical and chemical properties of the materials, it can be seen that the composite material specification is micron-level, the optimized injectable pearl / gelatin / bovine bone powder composite bone transplant material has a porous structure inside, and the pore size range is 75.94um~208.64um. Calcium-deficient apatite crystals are precipitated around the gelatin fibers attached to the surface, which mainly contain four elements: C, O, P and Ca. The Ca / P ratio is 4.05±0.18. The main components are HA, pearl powder, carbonated apatite and brushite. The injectability rate is 97.14±0.04%, the initial setting time is 7.21±0.04min, the final setting time is 12.89±0.26min, the degradation rate is 4.52±0.35%, and the compressive strength is 8.38±0.03MPa. All properties meet the clinical physical and chemical performance requirements and can be used for subsequent in vitro biological evaluation.
[0169] Experimental Example 4
[0170] In this experimental example, commercial bone transplant materials (produced by Beijing Paisheng Biotechnology Co., Ltd.) were selected as the control group, and injectable pearl / gelatin / bovine bone powder composite bone transplant materials (same as Example 3) were selected as the experimental group to compare and study their in vitro biological properties. All groups of materials were sterilized by γ rays (3kGy) before the experiment.
[0171] Mouse preosteoblasts (MC3T3-E1) were used to study the cell compatibility and cell-induced osteogenicity of the above materials. The revived cells were transferred to a 100 mm culture dish, and then 7 ml of complete cell culture medium (formula: 85% high glucose cell culture medium + 10% fetal bovine serum + 5% dual antibiotics) was added to the culture dish, and then placed in a cell incubator at a temperature of 37 ° C and a humidity of 100%. The cell culture medium was changed every 3 days. When the cell adhesion coverage rate in the culture dish reached about 80%, a certain number of cells were inoculated into the cell culture plate containing the material and incubated according to the experimental requirements to prepare for subsequent in vitro cell experiments.
[0172] It is noted that the data measured in the following experiments were subjected to univariate analysis and LSD test using SPSS26 statistical software (IBM, USA), and P<0.05 indicated that the difference was statistically significant. The data obtained from the analysis and processing were expressed in the form of mean ± standard deviation (Mean ± SD). The data graphs were drawn using GraphPad Prism 9.5 software (GraphPad Software, Inc., USA).
[0173] Cell Adhesion Assay:
[0174] The adhesion of cells on the surface of each group of sample materials was observed by SEM scanning electron microscope: The experimental steps are as follows:
[0175] (1) MC3T3-E1 cells were inoculated in 48-well cell culture plates containing materials from each group at a density of 2.5×10 4 Pieces / cm 2 Then add 150ul of culture medium to each well and place the cells in a constant temperature incubator for 24h.
[0176] (2) After 24 h of culture, the material was gently rinsed three times with PBS solution to remove cells that were not attached to the cell surface and residual culture medium.
[0177] (3) Add 100 μl of 4% paraformaldehyde solution to each well and react for 15 minutes at room temperature to fix the cells on the surface of the material.
[0178] (4) Use PBS solution to clean the excess paraformaldehyde solution on the surface of the material, and repeat 3 times.
[0179] (5) Dehydrate the samples using different concentrations of ethanol solutions (20%, 50%, 70%, 100%) for 10 min at each concentration, and dehydrate them twice in 100% ethanol solution.
[0180] (6) After dehydration, place in a 37°C electric constant temperature forced air drying oven and dry for 24 hours.
[0181] (7) The dried material with cells attached was placed on the surface of the conductive glue with tweezers, sprayed with gold for 300 s, and placed in a SEM for observation at an accelerating voltage of 15 kV. The overall adhesion of the material surface was observed at a magnification of 500, and the cell adhesion of the material surface was observed at a magnification of 3500.
[0182] The results are as follows Fig.11 As shown:
[0183] Fig.11 Schematic diagram of cell adhesion in each group of bone transplant materials, in which A / B is the SEM image of cell adhesion of the control group (commercial product) at 500 and 3500 times, C / D is the SEM image of cell adhesion of the experimental group (same as Example 3) at 500 and 3500 times, and the red arrow points to the MC3T3-E1 cell cluster.
[0184] The results show that MC3T3-E1 cells have good cell adhesion in both commercial bone powder and injectable pearl / gelatin / bovine bone powder composite bone transplant materials. The white granular substances on the surface of commercial bone transplant materials are MC3T3-E1 cells or cell clusters, and the black shadow areas on the surface of injectable pearl / gelatin / bovine bone powder composite bone transplant materials are adhered MC3T3-E1 cell clusters.
[0185] The adhesion of cells on the surface of materials is the first step in the reaction between cells and materials, which will affect the growth and proliferation of cells in the materials in the later stage. The pearl powder organic matter in the injectable pearl / gelatin / bovine bone powder composite bone transplant material can effectively promote cell adhesion. Gelatin as a viscosity agent can mediate cell adhesion. The pore structure of the injectable pearl / gelatin / bovine bone powder composite bone transplant material can increase the surface area of the material and also improve the adhesion of cells on the surface of the material.
[0186] Cell proliferation assay:
[0187] CCK-8 reagent was used to detect the number of cells after co-culture in the material for 1 day, 3 days, 5 days and 7 days, and the cell proliferation was analyzed: the cells were cultured at 5×10 3 cells / cm 2The density was inoculated into a 48-well cell culture plate containing each group of materials. The culture medium in the 48-well cell culture plate was regularly extracted at the above time points, and 150ul complete cell culture medium and 15uCCK-8 reagent were added to the wells. Only 150uL complete cell culture medium and 15uCCK-8 reagent were added to the blank control group. After the 48-well cell culture plate to which the CCK-8 reagent had been added was placed in a cell incubator for reaction for 1 hour, 100ul of stained cell supernatant per well in the 48-well cell culture plate was taken out and transferred to a 96-well cell culture plate. The optical density OD value of the cell supernatant in the 96-well cell culture plate was measured at 450nm using a microplate reader. The numerical value obtained after standardization of the blank control OD value represents the number of cells in the material at that time point.
[0188] The results are as follows Fig.12 As shown:
[0189] Fig.12 The figure is a schematic diagram of the proliferation of cells after culturing each group of materials for 1, 3, 5 and 7 days. In the figure, A represents the standardized OD value, and B represents the proliferation curve of the cells in each group of materials within 7 days. Fig.12 In A, yellow represents the blank group, blue represents the control group (commercially available product), and gray represents the experimental group (same as Example 3); Fig.12 In B, the dark purple square mark represents the blank group, the blue purple triangle mark represents the control group (commercial product), and the blue diamond mark represents the experimental group (same as Example 3).
[0190] The results show that the OD values and cell proliferation of MC3T3-E1 cells detected at different time points (1, 3, 5, and 7 days) after co-culture in the blank group, commercial bone graft material control group, and injectable pearl / gelatin / bovine bone powder composite bone graft material experimental group. Fig.12 A represents the standardized OD value, Fig.12 B shows the growth of cells in each group of materials. The results of the two groups of figures show that as time goes by, the number of cells co-cultured in each group of materials increases. The number of cells in the injectable pearl / gelatin / bovine bone powder composite bone graft material on the third day was 5.59±2.22 times that of the first day, which was less than the number of cells in the blank group (P<0.05) and greater than the number of cells in the control group (P<0.05). As the cell co-culture time increases, the number of cells in the injectable pearl / gelatin / bovine bone powder composite bone graft material proliferates to 30.15±3.26 times that of the first day on the seventh day, and the number of cells is greater than that in the blank group and the control group (P<0.05), which may be due to the pearl water-soluble matrix and gelatin organic matter contained in the pearl / gelatin / bovine bone powder composite bone graft material promoting cell proliferation.
[0191] Alkaline phosphatase relative activity level determination test:
[0192] The BCA protein concentration assay kit was used to detect the protein concentration after the cells and materials were co-cultured for 5 and 10 days, and the alkaline phosphatase activity assay kit was used to detect the relative activity level of ALP expressed by the cells after the cells were co-cultured with each group of materials for 5 and 10 days. The experimental steps are as follows:
[0193] (1) 5×10 3 Pieces / cm 2 The cells were seeded at a density of 100 μg / ml into a 48-well cell culture plate containing materials from each group.
[0194] (2) At 5 days and 10 days, the cell culture medium of the 48-well cell culture plate was extracted, and the residual culture medium in the cell culture plate was washed with PBS solution. 200uL Ripa cell lysis solution was added to each well to lyse the cells on the surface of the material as the test group.
[0195] (3) According to the instructions for use of the BCA protein concentration assay kit: prepare 8 groups of protein standard solutions with concentrations of 0, 0.025, 0.050, 0.100, 0.200, 0.300, 0.400, and 0.500 mg / mL.
[0196] (4) Take 20uL of protein standard solution of each concentration and cell solution at each time point into a 96-well cell culture plate, add 180uL of BCA working solution, place in a 37°C cell incubator for 30 minutes, and then use a microplate reader to measure the absorbance at 562nm. Draw a protein standard curve based on the absorbance of protein standard solution of each concentration, and calculate the cell protein concentration in the material at each time point based on the absorbance of the cell solution combined with the protein standard curve.
[0197] (5) According to the instructions for use of the alkaline phosphatase activity detection kit: 0.5 mm / mL phenol standard application solution was used as the standard control group, the cell solution lysed at each time point was used as the experimental group, and the buffer solution was used as the blank control group.
[0198] (6) Take 50uL of phenol standard application solution, cell solution and buffer solution respectively into a 96-well cell culture plate, add 150uL of colorimetric base solution to each well, and place in a 37°C shaking incubator for 2h. After the reaction, use a microplate reader to measure the absorbance at a wavelength of 405nm. According to the following enzyme activity definition formula, calculate the relative activity level of cell alkaline phosphatase in each group of materials, A is the measured absorbance value, C is 标准 is the concentration of phenol standard application solution, C 样品 The cell protein concentration in the material sample determined in step (4):
[0199]
[0200] The results are as follows Fig.13, Fig.14 As shown:
[0201] Fig.13 is the standard protein concentration curve obtained by measurement;
[0202] Fig.14 This is a schematic diagram of the protein concentration and ALP relative activity level measured and calculated after the cells were co-cultured with each group of materials for 5 and 10 days. In the figure, A represents the protein concentration of each group of materials, B represents the ALP relative activity level, ** represents P<0.01, and # represents P>0.05. Fig.14 In A, blue represents the blank group, brown represents the control group, and gray represents the experimental group; Fig.14 In B, black represents the blank group, dark blue represents the control group, and light blue represents the experimental group.
[0203] The standard protein concentration curve was obtained by measuring Fig.13 ) Calculate the protein concentration of each group of materials at 5 and 10 days ( Fig.14 A), the OD value of each group of materials was detected by ALP reagent detection kit and the relative activity level of ALP in each group of materials was calculated ( Fig.14 B), the results showed that: with the increase of time, the relative activity level of ALP in each group of materials increased, and the relative activity level of ALP in the experimental group increased from 1.23±0.04 to 1.79±0.04, which was higher than that in the control group and the blank group (P<0.01). ALP is an important marker for osteoblast differentiation, and the cell ALP activity level can reflect the osteogenic differentiation ability of cells on the surface of the material.
[0204] The reason why the injectable pearl / gelatin / bovine bone powder composite bone transplant material shows good differentiation into bone may be that the water-soluble matrix in the pearl improves the level of cell differentiation into bone. In this experiment, the pearl and bovine bone powder were compounded by low-temperature hydration to retain the activity of the water-soluble organisms in the pearl, making the injectable pearl / gelatin / bovine bone powder composite bone transplant material show a certain differentiation into bone ability.
[0205] In summary, it was observed that the surface of the injectable pearl / gelatin / bovine bone powder composite bone graft material (same as Example 3) had a cell adhesion ability similar to that of the commercial bone graft material, and a large number of MC3T3-E1 cells could be adhered; the number of cell proliferation in the composite bone graft material was higher than that of the commercial bone graft material and the blank group (P<0.05), and the number of MC3T3-E1 cells after 7 days was 30.15±3.26 times that of the first day (P<0.01); the relative activity level of ALP expressed by MC3T3-E1 cells in the injectable material increased from 1.23±0.04 to 1.79±0.04, which was significantly higher than that of the commercial bone graft material and the blank group (P<0.01), indicating that the injectable pearl / gelatin / bovine bone powder composite bone graft material has good in vitro biocompatibility and osteogenesis ability.
[0206] Experimental Example 5
[0207] Viscosity analysis of composite slurry:
[0208] The injectable bone graft material is a viscous fluid that can flow under the pressure of the syringe. In the above Experimental Examples 1 to 4, the sample materials used all adopt a solid-liquid ratio of 0.35 mL / g to prepare a composite slurry with good fluidity and adhesion.
[0209] This experiment used pure cattle bone powder slurry (cattle bone powder + citric acid solution) and pearl / cattle bone powder composite slurry (pearl / cattle bone powder and citric acid solution). Fig.15 shown.
[0210] Fig.15 The figure is a schematic diagram of the morphology of two slurries. In the figure, A is pure cattle bone powder slurry and B is pearl / cattle bone powder composite slurry.
[0211] It can be seen that the slurry formed by adding bovine bone powder to citric acid solution is a fluid with low viscosity: it may be that the HA in the small particle size bovine bone powder is not easy to dissolve in the liquid, and the Ca in HA 2+ It is not easy to form cross-linking entanglement with citric acid, which leads to low viscosity of bovine bone powder slurry, which is not easy to shape arbitrarily and cannot maintain a stable height at the transplant site. The slurry formed by adding pearl / bovine bone powder to citric acid solution is more viscous. Pearl / bovine bone powder is more soluble in the solution than pure bovine bone powder. Citric acid can react with Ca in pearl / bovine bone powder. 2+ More cross-linking bonds are formed, so that the pearl / bovine bone powder composite slurry has greater viscosity, can maintain a stable shape at the implantation site, can be cured in situ, and meet clinical requirements. Therefore, this application scheme selects the pearl / bovine bone powder composite slurry for key research.
[0212] In summary, the embodiments of the present application provide an injectable composite bone transplant material and a preparation method thereof, which uses bovine bone powder as a basic material for injectable modification. The prepared injectable composite bone transplant material has obvious improvements in osteogenesis efficiency, spatial stability, surgical convenience and cost compared with commercial bone powder, and its physicochemical and biological properties meet clinical needs, and it has better cell compatibility, cell adhesion and induction of cell osteogenesis. It has low cost and excellent performance, and has great application potential in maxillary sinus floor augmentation surgery.
[0213] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
Claims
1. An injectable composite bone graft material, characterized in that: The method comprises the following components: a mixed powder and a composite solution; Wherein, the raw materials of the mixed powder include cattle bone powder and pearl powder; The raw materials of the composite solution include gelatin solution and citric acid solution.
2. The injectable composite bone graft material according to claim 1, characterized in that: In the mixed powder, the mass ratio of pearl powder is 25-40%; In the composite solution, the volume ratio of the gelatin solution is 15-35%.
3. The injectable composite bone graft material according to claim 1, characterized in that: In the mixed powder, the cow bone powder is prepared by calcining and grinding cow femur, and the pearl powder is pharmaceutical grade pearl powder.
4. The injectable composite bone graft material according to claim 1, characterized in that: In the composite solution, the gelatin solution used is prepared from dry gelatin and has a concentration of 11.11%; The concentration of the citric acid solution used was 25%.
5. The injectable composite bone graft material according to claim 1, characterized in that: Among the raw material components, the solid-to-liquid ratio of the mixed powder to the composite solution is 0.35 mL / g.
6. A method for preparing an injectable composite bone graft material according to any one of claims 1 to 5, characterized in that: It includes the following steps: Preparation of cattle bone powder: Take cattle bones and remove impurities such as surface muscle, periosteum, fat, etc., boil them in water, soak them in sodium hydroxide solution and hydrogen peroxide solution respectively, wash them, calcine them, grind them and sieve them to obtain cattle bone powder for later use; Preparation of mixed powder: Mix the prepared cow bone powder and pearl powder in proportion to obtain a mixed powder for later use; Preparation of gelatin solution: weigh dry gelatin and add UP water to make the dry gelatin swell to a gel state, then perform constant temperature treatment to prepare a gelatin solution for later use; Preparation of composite solution: Mix the prepared gelatin solution with the citric acid solution in proportion to obtain a composite solution for later use; Product material preparation: The prepared mixed powder is mixed with the composite solution in proportion to obtain a composite slurry, and the composite slurry is then injected into a mold and then cured at a constant temperature to obtain the product injectable composite bone transplant material.
7. The method for preparing the injectable composite bone graft material according to claim 6, characterized in that: In the step of preparing the bovine bone powder, the concentration of the sodium hydroxide solution used is 1 mol / L, and the concentration of the hydrogen peroxide used is 30%.
8. The method for preparing the injectable composite bone graft material according to claim 6, characterized in that: In the step of preparing the cattle bone powder, calcination is carried out in a muffle furnace at 850° C., and then grinding is carried out in a planetary ball mill at a rate of 50 r / min, and the cattle bone powder is obtained after sieving.
9. The method for preparing the injectable composite bone graft material according to claim 6, characterized in that: In the gelatin solution preparation step, the gelatin solution is prepared by subjecting the solution to a constant temperature treatment in a 37° C. electric thermostat.
10. The method for preparing the injectable composite bone graft material according to claim 6, characterized in that: In the product material preparation step, the product is cured at a constant temperature in an electric constant temperature blast drying oven at a temperature of 37° C. and a humidity of 100% to obtain an injectable composite bone transplant material.
Citation Information
Patent Citations
Preparation method of rapid degradable injectable brushite bone cement
CN105288729A
Medical composite biological bone cement powder, bone cement liquid and composite biological bore cement
CN1403168A
Injectable bone implant compositions, kits, and related methods
WO2024137930A2